POLITIK KEBANGKITAN ADAT DALAM PRAKTEK WACANA ORANG AMBON - Batlayeri, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2022)
In Indonesia, the appearance of indigenous revivalism is equivalent to a number of unequal treatments at the local stage such as land seizure of idigenous lands to be coverted intothe consession of national development; this includes the conversions of negeri adat (indigenous villages) in Ambon which is the main locust of this study. The intention of indigenous revivalism is to struggle for native values and regain equality which were neglectedduring the New Order Regime and unfortunately has rooted in the discourse of power. The indigenous euphoria in this reformation era as a matter of fact did not meet with the challengesof native values, instead it is somehow stuck in the local political importances by making bureaucratization, managerialization, and/or administration of native values. Its consequence is that of ethnical projections. The indigenous revivalism discourse has changed into therevivalism discourse of ethnical identity. In that context, specialy of the revival indigenous discourse in Ambon, I would like to discuss three main issue, namely genealogy, powerrelation, and subjectivity. Discussion about the third issue will use the method of critical discourse analysis of Michel Foucault. Keywords: indigenous revivalism, indigenous villages, genealogy, power relation, and subjectivity.